Analisis Dampak Kesalahan Dalam Simulasi Manajemen Elektronik Mesin Pada Pengoperasian Kendaraan Bermotor - Yuliarman Saragih; Falentina Lavi; Kintania Pracipta; Ahmad Al-Baehaqi Salam; Puji Waluyo (Universitas Medan Area, 2022)
For internal combustion engine electrical management in order for an engine to function properly, all its electronic components must function and play their role. Failure of these electronic components may result in improper preparation of the fuel mixture. This also affects driving safety. The impact of individual errors can have a negative impact on traffic safety and can also have a negative impact on other participants. The subject of this study was to investigate the impact of failure of electronic components on selected operating characteristics. This article is to determine the failure rate of electronic mechanical components and can affect the operation of road vehicles. Eight electronic system faults are simulated with specific vehicles and use fuel assemblies in gasoline fuel. Measurements were made based on laboratory conditions that gave to change the characteristics of the vehicle handling between damage and corruption. Making the vehicle power parameters and the selected exhaust emission components are determined for the selected vehicle characteristics. The results show that the engine failure of the electronic system has a great impact on the operating characteristics, and at the same time there are situations in the normal operating state of the vehicle in which some of these defects are unknown to the vehicle operator ricefield. The results of the publication can be used in the fields of written law, production and operation of road vehicles, and mathematical modeling of gas emission production from road transportation.